Evaluation of Ho_{100-x-y}Er_{x}Ce_{y} magnetic refrigerants using advanced multisample neutron transmission spectroscopy - Hiroaki Mamiya; Noriki Terada; Simon Rosenqvist Larsen; Naohito Tsujii; Kosuke Hiroi; Takenao Shinohara; Hossein Sepehri-Amin (Physical Review Research)
Magnetic refrigeration represents an environmentally friendly and promising technology for cooling applications, particularly in hydrogen liquefaction. Recent advancements have demonstrated a highly efficient cooling protocol utilizing small magnetic-field oscillations near metamagnetic transitions, tested using pure holmium metal. This study investigates ternary alloys substituted with erbium and cerium, specifically Ho_{100-x-y}Er_{x}Ce_{y} (x<100, y<21), to further enhance the performance of the refrigerant. The control of magnetic entropy is largely dependent on identifying variations in spin configurations. However, analyzing these variations in ternary alloys through neutron diffractometry is time intensive. To address this challenge, a multisample neutron transmission spectroscopy technique was developed and applied at beamline 22 RADEN at Japan Proton Accelerator Research Complex (J-PARC). This approach enabled the simultaneous observation of transmission spectra for 25 different alloy compositions at cryogenic temperatures. The spectra revealed that cerium-doped, erbium-rich alloys primarily exhibit ferromagnetic components, yielding a magnetocaloric effect that exceeds that of pure holmium metal under a 5-T magnetic field. In other alloy compositions, the presence of antiferromagnetic ordered states was indicated by satellite Bragg edges in the spectrum. The magnetocaloric effects associated with metamagnetic transitions from these states tend to diminish as the transitions become more frequent or diffuse due to the alloying. The insights gained from this spectroscopic technique contribute to our understanding of the variations in magnetocaloric properties as a result of alloying. Moreover, the successful simultaneous determination of spin configurations across numerous samples highlights the potential of this spectroscopic approach for widespread use in magnetic property evaluation, particularly in the realm of big data-driven research.